G-Centre formation and behaviour in a silicon on insulator platform by carbon ion implantation and Proton irradiation - D.D. Berhanuddin,; N.E.A. Razak,; Lourenço, M.A.; B.Y. Majlis,; Homewood, K.P. (Penerbit Universiti Kebangsaan Malaysia, 2019)
The interest in the G-centre is driven by reports that it can lase in silicon. To further this, the transfer of this technology from bulk silicon to a silicon-on-insulator (SOI) platform is an essential requirement to progress to lasing and optical amplification on silicon. We report on the efficient generation of the lasing G-centre in SOI substrates by proton irradiation of carbon ion implants. Following carbon implantation samples were annealed and then proton irradiated to form the G-centre and characterized by photoluminescence measurements. The temperature dependence of the emission and the behaviour of the G-centre with post proton annealing were investigated and results are compared with identical implants in control samples of bulk silicon. Overall, we find that the optically active G-centre can be up to 300% brighter and has better survivability over a wider process window in SOI than in bulk silicon.